FAKTOR FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA PERAWAT PADA RSUD TNI AU YOGYAKARTA - Petrus Dala Wolo; Rina Trisnawati; Wiyadi Wiyadi (Jurnal Manajemen Dayasaing, 2015)
This study aims to determine the effect of salary, promotion, supervision, co-workers,the work itself, and the work environment to job satisfaction of nurses in the Air ForceRSP Dr. S. Hardjolukito Yogyakarta. The population in this study is a nurse in the AirForce RSP Dr. S. Hardjolukito Yogyakarta as many as 96 people. samples were takenas many as 71 nurses who served in inpatient units including Camar room, the Peacockroom, a cassowary room and parakeets room. The analytical method used in this studyusing linear regression berganda.Tteknik proposive sampling using sampling. Theresults showed that no significant relationship between the work itself and the workingenvironment on job satisfaction. Salary, supervision, and co-workers have no effect onjob satisfaction. While the campaign shows a negative relation to job satisfaction, workitself and the working environment.